PENERAPAN MODEL COOPERATIVE SCRIPT BERBANTUAN MEDIA ALAT PERAGA TARBOL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SD 1 JATI WETAN KUDUS - Puspitasari, Puteri (Jurnal Prakarsa Paedagogia, 2024)
A This research aims to describe (1) the application of the Cooperative Script learning model assisted by tarbol media in increasing the learning activity of class V students in science and soscial subjects at SD 1 Jati Wetan Kudus (2) the application of the Cooperative Script learning model assisted by tarbol media in improving teacher skills in science and soscial subjects for class V at SD 1 Jati Wetan Kudus, (3) the effect of implementing the Cooperative Script learning model assisted by tarbol media on increasing the classical learning completeness of class V students in science  and soscial subjects at SD 1 Jati Wetan Kudus. The conclusion of this research is that the application of the Cooperative Script model assisted by Tarbol media can increase the learning activity of class V students in science and soscial subjects at SD 1 Jati Wetan.